2018
DOI: 10.3390/ijms19051333
|View full text |Cite
|
Sign up to set email alerts
|

The Vast Complexity of the Epigenetic Landscape during Neurodevelopment: An Open Frame to Understanding Brain Function

Abstract: Development is a well-defined stage-to-stage process that allows the coordination and maintenance of the structure and function of cells and their progenitors, in a complete organism embedded in an environment that, in turn, will shape cellular responses to external stimuli. Epigenetic mechanisms comprise a group of process that regulate genetic expression without changing the DNA sequence, and they contribute to the necessary plasticity of individuals to face a constantly changing medium. These mechanisms act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 123 publications
0
8
0
4
Order By: Relevance
“…DNA methylation and histone acetylation are the most intensive studied epigenetic modifications in brain development [8, 9]. Recent studies report on the emerging role of histone methylations [10]. However, little is known about the implication of histone modifications specific for the development and function of the cerebellum.…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation and histone acetylation are the most intensive studied epigenetic modifications in brain development [8, 9]. Recent studies report on the emerging role of histone methylations [10]. However, little is known about the implication of histone modifications specific for the development and function of the cerebellum.…”
Section: Introductionmentioning
confidence: 99%
“…Las características sociodemográficas de los cuidadores pueden influir en la respuesta al estrés (2) por la cuarentena , a su vez modificar la interacción entre los cuidadores y los infantes, lo que afecta el (3)(4)(5)(6)(7)(8)(9)(10)(11) apego en vez de generar ansiedad en los infantes .…”
Section: Discussionunclassified
“…El estatus socio-económico bajo, incrementa el riesgo a exponerse a eventos/experiencias negativas relacionadas con el entorno donde viven, como pueden ser el desorden o inestabilidad familiar; estos eventos negativos en la vida generan un disregulación biológica similar a un estado inmune inflamatoria que conlleva a cambios epigenéticos en el neurodesarrollo de manera negativa, también crea el efecto de apagado, que disminuye la percepción de estímulos nocivos del entorno e incluye los estímulos adecuados, afectando los eje social y del (5)(6)(7)(8)(9)(10)(11) lenguaje , estas señales de retroalimentación intervienen con la maduración y polarización (12) neuronal adecuada para el neurodesarrollo ; por lo cual están relacionadas con el desarrollo de (13) trastornos mentales en el adulto .…”
Section: Introductionunclassified
“…I am very proud of the papers contributed to this section that consists of eight review articles by top-level epigenetic researchers in the world. Through this issue, readers will learn current epigenetic understanding of brain function, congenital NDs, and acquired NDs [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. More precisely, Cariaga-Martínez et al extensively described epigenetic properties in embryonic stem cells and throughout early development phases [ 12 ].…”
mentioning
confidence: 99%
“…Through this issue, readers will learn current epigenetic understanding of brain function, congenital NDs, and acquired NDs [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. More precisely, Cariaga-Martínez et al extensively described epigenetic properties in embryonic stem cells and throughout early development phases [ 12 ]. Ma et al revealed a microRNA involved in the pathogenesis of neonatal hypoxic-ischemic encephalopathy and its therapeutic use with complementary oligonucleotides of this microRNA [ 13 ].…”
mentioning
confidence: 99%